2′-O-Methylperlatolic Acid Enhances Insulin-Regulated Blood Glucose-Lowering Effect through Insulin Receptor Signaling Pathway. (23rd April 2022) - Yinghao, Wang; Qiaoli, Guan; Guanfu, Liu; Xiaoyun, Wu; Xuanjun, Wang; Jun, Sheng
Abstract : Purpose . Insulin receptor (InsR) sensitizers represent a new type of therapeutic agent for the treatment of diabetes, with 2 ′ -O-methylperlatolic acid (2-O-M) being a potential InsR targeting drug. The purpose of this study was to determine whether 2-O-M functions as an activator of the insulin signaling pathway, regulating glucose hemostasis through the InsR and exerting a glucose-lowering effect in an animal model of diabetes. Methods . SPR-based analyses were used to detect the binding of different concentrations of 2-O-M to the InsR. The protein levels of IR- β, p-IR, AKT, and p-AKT in Hepa and C2C12 cell lines and liver and muscle tissues were determined by western blotting. Glucose uptake capacity was determined in C2C12 cells. Streptozotocin-induced diabetic mice were randomly divided into four groups: the control, insulin treated, 2-O-M treated, and combined insulin and 2-O-M treated. Mice were injected with 2-O-M or normal saline and the average blood glucose concentration after 120 min, and the serum levels of insulin, glucagon, and C-peptide were measured. Next, qRT-PCR was performed to detect the mRNA expression of genes involved in lipid and glucose metabolism in the liver and muscle tissues. Results . 2-O-M binds to the extracellular domain of the InsR. Moreover, combination treatment with 2-O-M and insulin resulted in significant activation of the insulin signaling pathway in vitro and significant stimulation of the glucose uptake capacity of C2C12 myotubes. In mice with streptozotocin-induced diabetes, 2-O-M significantly prolonged the blood glucose-lowering effect of insulin, significantly reduced the secretion of exogenous insulin, and reduced the blood glucose concentration in vivo . In addition, treatment with 2-O-M alone significantly enhanced the phosphorylation of AKT in muscle tissue, which enhanced glucose uptake in C2C12 myotubes. Further, 2-O-M significantly increased glucagon secretion and enhanced liver gluconeogenesis to prevent hypoglycemia. Conclusion . 2-O-M enhances the hypoglycemic effect of insulin through the insulin signaling pathway and can be used as a complement to insulin. This synergetic effect may lower the required dose of insulin and protect β cells.